Modes of knowledge production: articulating coexistence in UK academic science - Klangboonkrong, Yiarayong (Cranfield University, 2015)
The notion of Mode 2, as a shift from Mode 1 science-as-we-know-it, depicts science as practically relevant, socially distributed and democratic. Debates remain over the empirical substantiation of Mode 2. In particular, our understanding has been impeded by the mutually exclusive framing of Mode 1/Mode 2. Looking at how academic science is justified to diverse institutional interests – a situation associated with Mode 2 – it is asked, “What happens to Mode 1 where Mode 2 is in demand?” This study comprises two sequential phases. It combines interviews with 18 university spinout founders as micro-level Mode 2 exemplars, and macro-level policy narratives from 72 expert witnesses examined by select committees. An interpretive scheme (Greenwood and Hinings, 1988) is applied to capture the internal means-ends structure of each mode, where the end is to satisfy demand constituents, both in academia (Mode 1) and beyond (Mode 2). Results indicate Mode 1’s enduring influence even where non-academic demands are concerned, thus refuting that means and ends necessarily operate together as a stable mode. The causal ambiguity inherent in scientific advances necessitates (i) Mode 1 peer review as the only quality control regime systematically applicable ex ante, and (ii) Mode 1 means of knowledge production as essential for the health and diversity of the science base. Modifications to performance criteria are proposed to create a synergy between modes and justify public investment, especially in the absence of immediate outcomes. The study presents a framework of Mode1/Mode 2 coexistence that eases the problem with the either/or perception and renders Mode 2 more amenable to empirical research. It is crucial to note, though, that this is contingent on given vested interests. In this study, Mode 1’s fate is seen through academic scientists whose imperative is unique from those of other constituents, thereby potentially entailing further struggles and negotiation.
Keywords: Mode 2; Knowledge production; UK academic science; Legitimacy; Means-ends; Causal ambiguity; Social construction; Opaque institutional field